ESTIMASI ASUPAN KAROTENOID PADA USIA DEWASA DI INDONESIA - Sefrina, Linda Riski; Briawan, Dodik; Sinaga, Tiurma; Permaesih, Dewi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2017)
The objective of this study was to estimate carotenoid intake of Indonesian adults. A cross-sectional study design was used in this study. Secondary data was analyzed from the national consumption survey 2014 that was conducted by Research and Development Department of Indonesia Health Ministry. The number of subjects were 86,036. Assessment of food consumption used food recall 1x24 hour. Carotenoid content was obtained from the various references that have been matched to survey’s food items. The total carotenoid intake was the sum of five carotenoid sub-classes (α-caroten, β-caroten, β-cryptoxanthine, lutein + zeaxanthine and lycopene). Median of total carotenoid intake was 551.62 µg/day. Intake of total carotenoid was significantly difference by subject characteristics (gender, age, area, education level, job) and food groups consumption (p<0.05).